A non-interventional, cross-sectional study to analyse the quality of life of infertile patients at rural medical college - Ahmed, Khan Farnaz Feroz; Naik, Amit S.; Naik, Saudamini A.; Vaje, Mugdha C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: World health organization (WHO) estimates that 60 to 80 million couples worldwide currently suffer from infertility and in India, of the 8.8% infertility prevalence, 6.7% women have primary infertility and 2.1% women have secondary infertility Objectives were to assess the quality of life of infertile patients and to appreciate the physical, mental, social, and psychological sufferings of infertile patients. Methods: The 54 sequential infertility patients visiting gynecology OPD at SMBT IMS were self-administered a pre-validated questionnaire having 26 questions, divided into 3 components 1. Physical and psychological health of infertile patients. 2. Marital relationships of infertile patients. 3. Self-assessment of social status. Results: Out of 54 responders, 32 participants were female and 22 were male. Maximum responders had Primary infertility. In our study 46% responders felt they were sad and depressed, and 37% feel infertility makes them angry in their physical, social and work life, 35% responders felt it was difficult to talk to their about infertility. The 24% had severe form of physical pain and discomfort and 48% people were dissatisfied with their sexual relationship, 46% felt uncomfortable and incomplete attending social situations like holidays and celebrations as they felt they were topic of discussion all the time. Conclusions: This study, hopes to generate an empathetic approach among the masses towards patients with infertility. It might help to highlight the need for separate infertility OPDs and to include a psychological counseling dimension to the treatment of infertility